1994
DOI: 10.1148/radiology.193.2.7972764
|View full text |Cite
|
Sign up to set email alerts
|

Temporal lobe epilepsy: presurgical localization with proton chemical shift imaging.

Abstract: NAA/Cho is an excellent marker for localizing the epileptogenic zone in TLE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

18
77
2
4

Year Published

1995
1995
2002
2002

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 145 publications
(101 citation statements)
references
References 1 publication
18
77
2
4
Order By: Relevance
“…Most studies included only a small number of patients, controls, or almost exclusively patients with MRI evidence for MTS. Some studies included patients suspected or proved to have bilateral independent TLE, a finding used to explain discordant or nonlateralized MRSI results [8,14]. The 1 H-MRSI sensitivity (55-65%) reported in the series by Connelly and associates [11] and Cross and colleagues [12], including some discordant lateralization, is nearly identical to our results.…”
Section: Mri (Diagnostic and Hv)-hv Lateralized 2 Additional Patientssupporting
confidence: 86%
See 3 more Smart Citations
“…Most studies included only a small number of patients, controls, or almost exclusively patients with MRI evidence for MTS. Some studies included patients suspected or proved to have bilateral independent TLE, a finding used to explain discordant or nonlateralized MRSI results [8,14]. The 1 H-MRSI sensitivity (55-65%) reported in the series by Connelly and associates [11] and Cross and colleagues [12], including some discordant lateralization, is nearly identical to our results.…”
Section: Mri (Diagnostic and Hv)-hv Lateralized 2 Additional Patientssupporting
confidence: 86%
“…1 H-MRSI-Our relatively low sensitivity with 1 H-MRSI lateralization contrasts with the nearly 100% sensitivity reported in some earlier studies, including our own [7][8][9]14,30,31].…”
Section: Mri (Diagnostic and Hv)-hv Lateralized 2 Additional Patientscontrasting
confidence: 85%
See 2 more Smart Citations
“…The reduction was reported either in absolute units or as a ratio to choline-containing compounds (Ch) and/ or creatine/phosphocreatine (Cr). Several recent reports have shown that NAA in the contralateral side is also reduced in many mTLE subjects [8,10,11], suggesting contralateral damage. Structural abnormalities of both hippocampi have also been detected in an autopsy study of TLE [12].…”
mentioning
confidence: 99%